Breaking the Chains of Slavery: Precarity, the Personal and the Political in Nkosinathi Sithole's Hunger Eats a Man. Issue 2 (2nd July 2020) - Stobie, Cheryl
Abstract : This article offers a literary analysis of a prize-winning South African novel, Hunger Eats a Man (2015), by Nkosinathi Sithole. I analyse the political and cultural history and sexual politics represented in the novel by employing a theoretical nexus of precarity studies as it intersects with feminist, subaltern and postcolonial studies, enabling challenges to Eurocentric models of the precariat. I outline the conditions creating the precarity of certain characters, textually compared to slavery, and the effects of the economic gap between the black middle class and the desperately poor, rural slum-dwellers. Poverty and the abuse of women are both seen as forms of inadmissible exploitation in the novel, although the text refutes the possibility of a natural alliance between the struggles against the two forms of oppression. Using the theoretical work of Pumla Dineo Gqola on rape, I focus on voice, perspective, agency, subversion and resistance in examining the novel's representations of sexual abuse, rape and violent retribution. I note the implications of the story-within-a-story revolutionary narrative about the starving poor occupying the homes of the wealthy. Finally, I analyse the effects of techniques that shape readers positively, offering an ethical dimension that allows for social change.